2018
DOI: 10.7189/jogh.08.010501
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities for adolescent health in low- and middle-income countries: A mixed-methods synthesis of two separate exercises

Abstract: BackgroundIn order to clarify priorities and stimulate research in adolescent health in low- and middle-income countries (LMICs), the World Health Organization (WHO) conducted two priority-setting exercises based on the Child Health and Nutrition Research Initiative (CHNRI) methodology related to 1) adolescent sexual and reproductive health and 2) eight areas of adolescent health including communicable diseases prevention and management, injuries and violence, mental health, non-communicable diseases managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…While our sample reflects the demographic profile of HIV and other chronic disease services in South Africa, 1 , 36 with younger people reluctant to utilize adult-oriented services, 37 it is a cause for concern as young people are particularly vulnerable to mental health and substance use problems. 38 Future studies should consider how to expand the mental health counseling services available in PHC settings to other settings where young people are likely to seek health and social care. Nonetheless, despite some limitations, this qualitative study helped identify factors critical to consider when designing patient-centered mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…While our sample reflects the demographic profile of HIV and other chronic disease services in South Africa, 1 , 36 with younger people reluctant to utilize adult-oriented services, 37 it is a cause for concern as young people are particularly vulnerable to mental health and substance use problems. 38 Future studies should consider how to expand the mental health counseling services available in PHC settings to other settings where young people are likely to seek health and social care. Nonetheless, despite some limitations, this qualitative study helped identify factors critical to consider when designing patient-centered mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent priority setting exercises were conducted for three health areas – (1) maternal, (2) newborn and (3) child health. Adolescent health was not included because a priority setting exercise had recently been conducted and the results included questions that pertained to SBCE interventions [ 10 ]. A mixed-methods approach was used, which combined an adapted version of the Child Health and Nutrition Research Initiative (CHNRI) methodology [ 11 ] with a qualitative, consensus-building approach with experts.…”
Section: Methodsmentioning
confidence: 99%
“…Concerted effort is required to ensure research addresses these gaps. Global research priorities have recently been set for maternal and perinatal health [ 7 ], newborn health [ 8 , 9 ], and adolescent health [ 10 ]; some SBCE research priorities were identified within these exercises. However, a research agenda specifically for SBCE interventions for MNCH could better direct research towards the most important gaps in this field.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in 2016, in America, 333,000 adolescents exhibited co-occurrence of mental health disorders and substance abuse (Substance Abuse and Mental Health Services Administration, 2017). The World Health Organization urges recognition of the need to address mental health and substance abuse issues in adolescents' health and has set priority of place for adolescents' health in schools, primary care settings, communities, parenting, virtual media, and among peers (Nagata et al, 2018). Therefore, the political will from governments and international agencies should be supported, as each sector has an important role in promoting mental health and contributing to prevention and early intervention for adolescents experiencing mental health problems and alcohol abuse (Whiteford, Degenhardt, Murray, Vos, & Lopez, 2014).…”
Section: Common Sociodemographic and Health-related Variablesmentioning
confidence: 99%